Overall migration in microwaveable pre-package sandwich containers from conveniece stores in Metro Manila, Philippines - Salvador, Patricia Rose C.; Francisco, Ma. Leonora DL. (Quezon City College of Home Economics, University of the Philippines Diiman, 2019)
This study was done to assess the safety of microwaveable sandwich packaging used by convenience stores in Metro Manila, Philippines, based on their overall migration values at the start and end of their specified shelf life. Migration in food contact materials occur when substances (e.g. monomers, additives) diffuse from the packaging material and into the food surface. The presence of migrants in food products can result in quality deterioration and can present potentially harmful effects on consumer health. Three samples of microwaveable pre-packaged sandwiches available in convenience stores were tested for overall migration (OM). Packaging of the representative samples consisted of either polypropylene (PP) film, polyethylene terephthalate (PET) film, or paper lined with low-density polyethylene (LDPE). OM testing was done using the total immersion method, wherein samples were exposed to 10% (v/v) and 95% ethanol (v/v) at testing conditions of 2 hours at 70 °C. OM values for purely polymeric food packaging, namely PP and PET films, were found to be within OM limits set by the EU and US FDA of 10 mg/dm2 and 7.75 mg/dm2, respectively. However, paper/LDPE packaging did not pass the set limits for OM, with OM values particularly high following prolonged exposure to fatty food simulant, 95% ethanol. No correlation was found between storage time or the shelf-life of pre-packaged sandwiches with OM values, regardless of packaging material. It is recommended that both OM and specific migration be conducted for microwaveable food products that are high-fat and high-sugar, or are packaged using polymeric materials with low distortion and melting points, as there is a risk of obtaining high migration values.
Thesis (B.S. in Food Technology)---University of the Philippines Diliman
Keywords: Microwave food products; Sandwiches -- Packaging; Food -- Packaging; Plastics in packaging